2009
DOI: 10.1523/jneurosci.1544-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Canonical 5 Channels Activate Ca2+/Calmodulin Kinase Iγ to Promote Axon Formation in Hippocampal Neurons

Abstract: Functionality of neurons is dependent on their compartmentalized polarization of dendrites and an axon. The rapid and selective outgrowth of one neurite, relative to the others, to form the axon is critical in initiating neuronal polarity. Axonogenesis is regulated in part by an optimal intracellular calcium concentration. Our investigation of Ca 2ϩ -signaling pathways involved in axon formation using cultured hippocampal neurons demonstrates a role for Ca 2ϩ /calmodulin kinase kinase (CaMKK) and its downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
78
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 92 publications
(139 reference statements)
4
78
1
Order By: Relevance
“…In this study, transient receptor potential canonical 5 channel (TRPC5) activation stimulated axon elongation via CaMKI␥ (Davare et al, 2009). Some of the findings of Davare et al (2009) are consistent with those of Ageta-Ishihara et al (2009); both groups observed that pharmacological inhibition of CaMKK or knockdown of CaMKI or CaMKK blocked axon elongation and that deficits in axon elongation could be rescued by expression of constitutively active CaMKI. However, the studies disagree on the specific CaMKI isoform responsible for axon elongation.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…In this study, transient receptor potential canonical 5 channel (TRPC5) activation stimulated axon elongation via CaMKI␥ (Davare et al, 2009). Some of the findings of Davare et al (2009) are consistent with those of Ageta-Ishihara et al (2009); both groups observed that pharmacological inhibition of CaMKK or knockdown of CaMKI or CaMKK blocked axon elongation and that deficits in axon elongation could be rescued by expression of constitutively active CaMKI. However, the studies disagree on the specific CaMKI isoform responsible for axon elongation.…”
supporting
confidence: 90%
“…In contrast to Ageta-Ishihara et al (2009), another recent publication in The Journal of Neuroscience reported that CaMKI␥ is responsible for axonal rather than dendritic elongation in hippocampal cultures (Davare et al, 2009). In this study, transient receptor potential canonical 5 channel (TRPC5) activation stimulated axon elongation via CaMKI␥ (Davare et al, 2009).…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…The mechanism of activation is dependent on activation of PLC by guidance cues, which in turn leads to the production of IP 3 and Ca 2+ release from ER. Depletion of these stores opens the TRPC and Ca 2+ influx occurs (Davare et al 2009). …”
Section: Neurite Outgrowth and Dysregulated Calcium Signaling In Neurmentioning
confidence: 99%